Improved Capacitor Voltage Balancing Algorithm for a Single-phase T-type Inverter - Vu, Hoang Phuong; Kieu, Huu Phuc; Tran, Van Phuong; Nguyen, Dinh Ngoc; Nguyen, Quang Dich (JST: Engineering And Technology For Sustainable Development, 2021)
The paper proposes an improved pulse width modulation algorithm to solve the voltage imbalance on DC capacitors for single-phase T-type inverter. By changing the modulation index, the residual states can be applied to the discharge/charge state on the DC capacitors to balance the voltage. The proposed algorithm is validated for application in single-phase T-type inverters in independent mode. The simulation and experimental results have confirmed the effectiveness of the improved pulse width modulation method for single-phase T-type inverter.